Simulation-Based Mastery Learning with Deliberate Practice Improves Clinical Performance in Spinal Anesthesia - Udani, Ankeet D. (Hindawi Publishing Corporation, 2014)
Introduction. Properly performing a subarachnoid block (SAB) is a competency expected of anesthesiology residents. We aimed to determine if adding simulation-based deliberate practice to a base curriculum improved performance of a SAB. Methods. 21 anesthesia residents were enrolled. After baseline assessment of SAB on a task-trainer, all residents participated in a base curriculum. Residents were then randomized so that half received additional deliberate practice including repetition and expert-guided, real-time feedback. All residents were then retested for technique. SABs on all residents' next three patients were evaluated in the operating room (OR). Results. Before completing the base curriculum, the control group completed 81% of a 16-item performance checklist on the task-trainer and this increased to 91% after finishing the base curriculum (P < 0.02). The intervention group also increased the percentage of checklist tasks properly completed from 73% to 98%, which was a greater increase than observed in the control group (P < 0.03). The OR time required to perform SAB was not different between groups. Conclusions. The base curriculum significantly improved resident SAB performance. Deliberate practice training added a significant, independent, incremental benefit. The clinical impact of the deliberate practice intervention in the OR on patient care is unclear.